2021
DOI: 10.1016/j.jtauto.2021.100121
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of hospital readmissions and related factors in patients with autoimmune diseases

Abstract: Objective Autoimmune diseases generate an impact on the morbidity and mortality of patients and are a burden for the health system through hospital admissions and readmissions. The prevalence of readmission of patients with these diseases has not yet been described as a group, but rather as sub-phenotype. The objective of this study is to determine the prevalence of hospital readmissions in a Colombian population with autoimmunity and the factors related to readmission. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
0
1
0
1
Order By: Relevance
“…Prior hospitalization within 3 months was identified as an independent predictor of mortality in the current study. Consistent with previous findings, patients with SLE required frequent readmission, with disease activity as the primary reason for readmission ( 28 ). Previous studies have identified numerous risk factors associated with repeated remission, including disease flares, lupus nephritis, serositis, and thrombocytopenia.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Prior hospitalization within 3 months was identified as an independent predictor of mortality in the current study. Consistent with previous findings, patients with SLE required frequent readmission, with disease activity as the primary reason for readmission ( 28 ). Previous studies have identified numerous risk factors associated with repeated remission, including disease flares, lupus nephritis, serositis, and thrombocytopenia.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, patients who required readmission within a short period of time had more severe clinical manifestations than those who did not ( 6 , 29 ). Both disease activity and intensive immunosuppressive therapy make patients with SLE more susceptible to infection, contributing to increases in in-hospital mortality ( 28 ). Taken together, the available evidence highlights the importance of outpatient care, adherence to treatment, and patient education to reduce the risk of readmission and death.…”
Section: Discussionmentioning
confidence: 99%
“… 4 Similarly, the global prevalence of autoimmune diseases is approximately 3%, up to 25% require hospitalization and, of these, above 30% call for ICU admission. 5 The same is true for malignant tumors, with one malignancy diagnosis in every six patients treated in European ICUs. 6 Immunocompromise is defined as having a weakened immune system with less resistance to infections and more fragility to some comorbidities.…”
Section: Introductionmentioning
confidence: 93%
“…Since the last summary of evidence about the topic [ 2 ] several publications sustaining the theory have been published [ [1] , [2] , [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , <...…”
Section: Introductionunclassified